Confidence level and reliability analysis of the fatigue life of CFRP laminates predicted based on fracture fatigue entropy. (March 2022) - Huang, Jia; Yang, Hongsheng; Liu, Wencheng; Zhang, Kai; Huang, Aijun
Abstract: This study provides a novel methodology to evaluate fatigue life with the consideration of both confidence level and reliability for CFRP laminates by combining fracture fatigue entropy (FFE) theory and knowledge of statistics. After carrying out distribution analysis and statistical hypothesis testing, it is found that the FFEs obey well to log-normal distribution and the average values and deviations of logarithmic FFEs under different stress levels exhibit no obvious difference. The γ - p - S - N curves are predicted by single side allowance factor analysis and the prediction is found to be more conservative and have a larger scatter comparing to experimental results. Highlights: The correlation coefficients show FFE data obey well to log-normal distribution. The FFE values under different stress levels exhibit no obvious different. A new method based on statistical analysis is developed to predict p-r-S-N curves. The predicted p-r-S-N curves are conservative comparing to experimental ones.